Pendampingan Guru dalam Implementasi Model Project-Based Learning (PjBL) Berbasis Fenomena pada Pembelajaran Statistika di MA Muhammadiyah 1 Malang - Nourma Pramestie Wulandari; Husnul Khotimah (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
This community service activity aimed to assist a teacher in implementing a Project-Based Learning (PjBL) with phenomenon model in statistics instruction at MA Muhammadiyah 1 Malang. The main issue faced by the partner was the limited ability to design contextual learning experiences that connect statistical concepts to real-world phenomena. To address this issue, a mentoring program was conducted through workshops, lesson planning, classroom implementation, observation, and reflection. The program involved one model teacher in an initial intensive implementation stage. Data were collected through field notes, observations, teacher reflections, and documentation of classroom activities and students’ work. The results indicate that the teacher understood and implemented the PjBL model effectively. Students also showed active engagement, particularly in exploring, analyzing, and interpreting data from real-world contexts. The activity contributed positively to improving the teacher’s instructional practices and provided more meaningful learning experiences for students. Therefore, similar mentoring programs can serve as an effective strategy to support the implementation of innovative teaching practices in schools.